Minigene Splicing Assays Identify 12 Spliceogenic Variants of BRCA2 Exons 14 and 15 - Fraile-Bethencourt, Eugenia; Valenzuela-Palomo, Alberto; Díez-Gómez, Beatriz; Caloca, María José; Gómez-Barrero, Susana; Velasco, Eladio A. (Frontiers in Genetics, 2019)
A relevant fraction of BRCA2 variants is associated with splicing alterations and with an increased risk of hereditary breast and ovarian cancer (HBOC). In this work, we have carried out a thorough study of variants from BRCA2 exons 14 and 15 reported at mutation databases. A total of 294 variants from exons 14 and 15 and flanking intronic sequences were analysed with the online splicing tools NNSplice and Human Splicing Finder. Fifty-three out of these 294 variants were selected as candidate splicing variants. All variants but one, were introduced into the minigene MGBR2_ex14-20 (with exons 14 to 20) by site-directed mutagenesis and assayed in MCF-7 cells. Twelve of the remaining 52 variants (23.1%) impaired splicing at different degrees, yielding from 5% to 100% of aberrant transcripts. Nine variants affected the natural acceptor or donor sites of both exons and three affected putative enhancers or silencers. Fluorescent capillary electrophoresis revealed at least ten different anomalous transcripts: ▼(E14q5), ∆ (E14p10), ∆(E14p246), ∆(E14q256), ∆(E14), ∆(E15p12), ∆(E15p13), ∆(E15p83), ∆(E15) and a 942-nt fragment of unknown structure. All transcripts, except for ∆(E14q256) and ∆(E15p12), are expected to truncate the BRCA2 protein. Nine variants induced severe splicing aberrations with more than 90% of abnormal transcripts. Thus, according to the guidelines of the American College of Medical Genetics and Genomics, eight variants should be classified as pathogenic (c.7008-2A>T, c.7008-1G>A, c.7435+1G>C, c.7436-2A>T, c.7436-2A>G, c.7617+1G>A, c.7617+1G>T and c.7617+2T>G), one as likely pathogenic (c.7008-3C>G) and three remain as variants of uncertain clinical significance or VUS (c.7177A>G, c.7447A>G and c.7501C>T). In conclusion, functional assays by minigenes constitute a valuable strategy to primarily check the splicing impact of DNA variants and their clinical interpretation. While bioinformatics predictions of splice site variants were accurate, those of enhancer or silencer variants were poor (only 3/23 spliceogenic variants) which showed weak impacts on splicing ( 5 to 16% of aberrant isoforms). So, the Exonic Splicing Enhancer and Silencer (ESE and ESS, respectively) prediction algorithms require further improvement.